2019
DOI: 10.1093/hmg/ddz268
|View full text |Cite
|
Sign up to set email alerts
|

Atonal homolog 7 (ATOH7) loss-of-function mutations in predominant bilateral optic nerve hypoplasia

Abstract: Optic nerve hypoplasia (ONH) is a congenital optic nerve abnormality caused by underdevelopment of retinal ganglion cells (RGCs). Despite being a rare disease, ONH is the most common optic disc anomaly in ophthalmological practice. So far, mutations in several genes have been identified as causative, however many cases of ONH remain without a molecular explanation. The early transcription factor atonal basic-helix-loop-helix (bHLH) transcription factor 7 (ATOH7) is expressed in retinal progenitor cells and has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 80 publications
(82 reference statements)
3
22
1
Order By: Relevance
“…Human nonsyndromic congenital retinal nonattachment (NCRNA) disease is characterized by optic nerve aplasia, with profound secondary retinovascular and other ocular defects ( 26 , 27 ). The clinical phenotype overlaps autosomal recessive persistent hyperplastic primary vitreous (arPHPV) and vitreoretinal dystrophy, which are caused by point mutations in the ATOH7 coding sequence ( 18 , 26 , 28 , 29 ), and findings in Atoh7 mutant mice ( 16 , 17 , 30 ). NCRNA is caused by a 6.5-kb deletion, extending from 19.2 to 25.7 kb upstream of the TSS.…”
mentioning
confidence: 99%
“…Human nonsyndromic congenital retinal nonattachment (NCRNA) disease is characterized by optic nerve aplasia, with profound secondary retinovascular and other ocular defects ( 26 , 27 ). The clinical phenotype overlaps autosomal recessive persistent hyperplastic primary vitreous (arPHPV) and vitreoretinal dystrophy, which are caused by point mutations in the ATOH7 coding sequence ( 18 , 26 , 28 , 29 ), and findings in Atoh7 mutant mice ( 16 , 17 , 30 ). NCRNA is caused by a 6.5-kb deletion, extending from 19.2 to 25.7 kb upstream of the TSS.…”
mentioning
confidence: 99%
“…3,5,6 Likewise, an increasing number of studies highlight ATOH7 as an emerging candidate for eye diseases in humans. Variations in the ATOH7 locus have been associated with optic nerve hypoplasia (ONH) and aplasia (ONA), [8][9][10][11] further pointing towards the crucial role of atoh7 in RGC genesis and optic nerve development. Remarkably, a number of studies have also emerged, which highlight ATOH7 variants as associated with multiple eye disease traits.…”
Section: Introductionmentioning
confidence: 99%
“…In tetrapods, barhl2 (previously named MBH1 and XBH1) is expressed in both amacrine cells and RGCs of the developing and mature retina 12,13 . Studies have also reported that Barhl2 is both sufficient and essential for determining the subtype specific identity of amacrine cells as well as to promote the maturation and survival of RGCs downstream of Atoh7 (also known as Ath5) -a bHLH transcription factor required for the specification of RGCs in vertebrates [12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%